Dental status of children of early and preschool age in Moscow - O. M. Davidian; N. S. Tuturov; E. M. Shimkevich; E. A. Lukianova; O. V. Pilshchikova; Hayan Almokaddam; E. N. Kulaga; P. A. Terenteva (Эндодонтия Today, 2024)
INTRODUCTION. Conducting an epidemiological survey allows us to obtain reliable initial data on the level of prevalence and intensity of dental diseases, identify priority needs for providing all types of dental care to children, plan and implement dental programs, focusing on the initial dental status of the child population at different age periods.AIM. To study the dental status of children of early and preschool age based on data from a cross-sectional epidemiological study.MATERIALS AND METHODS. A cross-sectional epidemiological survey of the child population was conducted as part of preventive medical examinations of minors to study the dental morbidity of children of early (1–3 years) and preschool (4–6 years) age in Moscow. The study involved 1470 Moscow children aged 1 to 6 years old. The results of the survey were processed statistically.RESULTS. Data analysis showed that the indicator of the need for oral sanitation tends to increase as children grow older. A statistically significant dependence of the need for rehabilitation on the age group was revealed. The indicator of previously sanitized children is variable at different age periods. The rate of natural sanitation decreases as children grow older. A statistically significant dependence of natural sanitation on the age group was revealed. Categorical variables (absolute and relative) of the need for sanitation are higher among girls in all age groups and lower among boys. But statistically significant differences in the need for sanitation in boys and girls were observed only in the age group 1 year, 3 years and 5 years. In the age groups of 2, 4 and 6 years, there was a similar need for sanitation among boys and girls; no statistically significant differences were identified, despite the fact that categorical variables (absolute and relative indicators) indicated a higher need for sanitation of the oral cavity in girls than boys.CONCLUSIONS. Categorical (absolute and relative) variables indicate that the need for oral sanitation in girls is higher than in boys at all age periods.